An Initial Study on Integrating Cultural Heritage into Children's Education: The Case of Stone Carvings from the Southern Dynasties in China - Zhu Zhenya; Mo Yunjie; Fauzi Naeim; Liu Dongyu (Ilmu Inovasi Nusantara, 2025)
The stone carvings of the Southern Dynasties are outstanding representatives of ancient Chinese sculpture art. This study takes the Southern Dynasties stone carvings as an example to explore the feasibility of integrating cultural heritage into the field of children's education. The research focuses on the cognitive development characteristics of children, and designs a teaching practice activity that integrates field visits to cultural heritage, interactive experiences of digital products, handmade cultural and creative products, and storytelling of cultural heritage. A comparative experiment is conducted on students from a primary school in Nanjing. Through comparative analysis of data such as questionnaire surveys, interview observations, and test scores, it was found that integrating cultural heritage into children's education can not only significantly improve students' mastery of cultural heritage knowledge, but also effectively stimulate their enthusiasm for self-directed learning and active exploration. The experimental results have verified the positive role of integrating cultural heritage into children's education, providing a novel implementation path for the reform and innovation of children's education.